2010
DOI: 10.1103/physrevb.82.115114
|View full text |Cite
|
Sign up to set email alerts
|

Local spin susceptibility in the zero-gap-semiconductor state ofα(BEDT-TTF)2I3probed by

Abstract: ␣-͑BEDT-TTF͒ 2 I 3 has a double column structure with three crystallographically independent molecules, A, B, and C, and becomes an insulator below 135 K due to a charge-ordering ͑CO͒ transition. The CO state is suppressed under pressure and shows weak temperature dependence of the electrical resistance. The decline of the carrier density is observed over 1.8 GPa, suggesting a zero-gap-semiconductor state under high pressure. The local susceptibility on each site provides important information about the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Recently, it was pointed out that the Knight shift had not only the contribution from on-site local spin susceptibility but also one from the neighboring molecules in the paramagnetic phase of α -(BEDT-TTF) 2 IBr 2 19 and there was the discrepancy between the disproportionation estimated by the Knight shift determined from the state at Fermi energy and one estimated by the chemical shift determined from all states below Fermi energy in the paramagnetic phase of α-(BEDT-TTF) 2 I 3 . 20 Therefore, to estimate the degree of charge disproportionation in the CO state, we should use the chemical shift. At the AF phase of (TMTTF) 2 SbF 6 , a axis, b axis, and c * axis were assigned as the spin hard axis, the easy axis, and the intermediate axis, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was pointed out that the Knight shift had not only the contribution from on-site local spin susceptibility but also one from the neighboring molecules in the paramagnetic phase of α -(BEDT-TTF) 2 IBr 2 19 and there was the discrepancy between the disproportionation estimated by the Knight shift determined from the state at Fermi energy and one estimated by the chemical shift determined from all states below Fermi energy in the paramagnetic phase of α-(BEDT-TTF) 2 I 3 . 20 Therefore, to estimate the degree of charge disproportionation in the CO state, we should use the chemical shift. At the AF phase of (TMTTF) 2 SbF 6 , a axis, b axis, and c * axis were assigned as the spin hard axis, the easy axis, and the intermediate axis, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1(a)]. Sharp NMR spectra split by the dipolar interaction were observed above T CO ≈ 135 K, reflecting the four molecular sites in the unit cell [8,10]. The line positions exhibit large angular dependence on varying the field direction ψ [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At ambient P, the Dirac cones are likely present at high T, since recent 13 C-NMR studies found, in the local spin density i, a large difference among nonequivalent sites i (= A, A', B, and C) -B < A (= A') < C -with strong T dependence. It has been revealed that this feature is characteristic for the high-energy part of the DF-type excitations in a tilted Dirac-cone system like -I3 [8][9][10][11][12]. However, the presence of the low-energy linear spectrum near EF is hidden at low T beneath the first-order chargeordering (CO) transition taking place at TCO ≈ 135K [1,3,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] due to strong electron correlations [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The local DOS at each molecular site can be estimated by applying the present analyses to the published data [25]. Even though the absolute values are different from those in NH 4 and Rb salts because of the difference in band structure, we can clearly conclude that the local DOS at the B site is much smaller than that at the A site, and comparable to the value for the C site, as shown in Fig.…”
mentioning
confidence: 59%
“…In the Rb salt, 1/T 1 T decreases abruptly below 12 K due to the CDW transition, while NH 4 salt is in the Fermi liquid state down to the lowest temperature measured (4 K). The DOS at the Fermi surface vanishes in the CDW state, and becomes comparable to the [25]. The DOS at the B site is comparable to that at the C site.…”
mentioning
confidence: 89%